BUDAYA POLITIK LOKAL DAN PARTISIPASI POLITIK MASYARAKAT DI DESA SUMBER SARI KECAMATAN SEBULU DALAM PELAKSANAAN PEMILIHAN UMUM LEGISLATIF TAHUN 2014. - adi sucipto (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2015)
The purpose of this study was to determine the type of political culture, the type of political participation, political and cultural influences on the level of political participation of the people in the village of Sumber Sari subdistrict Sebulu. This study focused on the level of community participation in the village of Sumber Sari subdistrict Sebulu in the General Election 2014 Legislative method used in this research is descriptive quantitative method that factually describes the actual situation and the variables studied are descriptive with quantitative approach. Techniques used for data collection by using the method of Observation, Research Library, and the spaciousness to jump directly distributing questionnaires to a sample of the community. For seats the information in accordance with its function, the use of frequency distribution data analysis are then processed again by using cross-tabulation (crosstab), and chi-square. Given the circumstances and conditions of the people in the village of Sumber Sari after the research is done, and after analyzed the discovery proves that there isn’t a significant relationship between local political culture to the level of political participation of the community in the implementation of the General Election 2014 General Legislative, see the society's political culture largely classified have a political culture servant (subject political culture), which reached 64.95%, the remaining approximately 19.59% belong to a civilized society political participants (participant political culture), and the remaining 15.46% is classified as a civilized society parochial politics (parochial political culture ). People who belong to the civilized society of political participants may be affected other people, while the people who belong to the community even more parochial political culture is autonomous and not mobilized others.Key words: Culture Local Politics, and Society Political Participation.